Beneficial Impact of Vaccination Against SARS-CoV-2 on the Mental Health of IPF Patients - Ioannis Tomos; Andriana I. Papaioannou; Zoe I. Daniil; Ilias E. Dimeas; Paraskevi Kirgou; Athena Gogali; Konstantinos Tatsis; Ilias Papanikolaou; Vasilios Tzilas; Argyrios Tzouvelekis; Panayiota Tsiri; Paschalis Steiropoulos; et al. (Advances in Respiratory Medicine)
Background: Depression and anxiety represent significant comorbidities in idiopathic pulmonary fibrosis (IPF) patients, affecting their quality of life. The COVID-19 pandemic has had an uneven impact on global mental health. The Hospital Anxiety and Depression Scale (HADS) constitutes a validated tool to identify anxiety disorders and depression. The aim of this multicentre study was to evaluate the effect of COVID-19 vaccination on depression and anxiety in IPF patients. Methods: Consecutive IPF patients (median 73.5 years) who are regularly followed-up with were included in the study. Demographics, functional, and clinical were recorded. The HADS score was calculated before and one month after vaccination against COVID-19 in all participants. A Wilcoxon signed ranks test was conducted. Results: A total of 180 IPF patients (median 73.5 years) were included in the study. Among them, 145 patients (81%) received antifibrotic treatment. A significant reduction in HADS, both in anxiety and depression scales, was observed one month after vaccination against SARS-COV-2), independent of age, smoking, lung function impairment, and prior history of depression (p < 0.01). Conclusions: A higher Hospital Anxiety and Depression Scale score was detected before vaccination against COVID-19. It seems that vaccination also offered a beneficial effect on depression and anxiety in IPF patients, independent of age, smoking, lung function impairment, and prior history of depression.